PENTINGNYA KURIKULUM DALAM PROSES PEMBELAJARAN DI SMPIT FATAHILLAH CIREBON - liliekroudlotuljannah Lilik; Yeyet Nurhasanah; Muhammad Fahmi; Taufiq Nurrohman; Ahmad Latif Mujtahid (Al Naqdu, 2021)
This study aims to find out how important the curriculum is in the learning process at SMPIT Fatahillah Cirebon. This research uses qualitative research methods, based on descriptive studies. The result show that the curriculum plays an important role in the learning process at SMPIT Fatahillah Cirebon in order to create a structured learning atmosphere, facilitate educators in the teaching and learning process, facilitate educators in the process of making Learning Implementation Plans (RPP) and also so that schools and educators have achievement targets in learning. The curriculum at SMPIT Fatahillah Ciebon uses an internal curriculum and the curriculum is still in the process of being developed by the foundation team